2008
DOI: 10.1177/0020872807085859
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on social work's identity

Abstract: English Can we identify common themes characterizing the social work profession across cultures? Using Italian social workers' representations of their profession three core issues are identified that recur in international debates. Reconciling contradictory elements might be one of the common characteristics of the social work project across different countries. French Peut-on identifier des thèmes communs caractérisant les professions sociales à travers les cultures? En utilisant les représentations des t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Het vierde terrein neemt de professie van de sociaal werker onder de loep. Men verricht onderzoek naar de identiteit van de sociaal werker, de beroepsopvatting, of de percepties over de eigenheid van de sociaal werker tegenover andere praktijkdisciplines, zoals huisartsen, verpleegkundigen, psychologen of therapeuten (Fargion, 2008;Scholte, 2010;Weiss-Gal & Welbourne, 2008). Een belangrijke vraag binnen dit onderzoek betreft de identiteit van de sociaal werk professie.…”
Section: H E T T E R R E I Nunclassified
“…Het vierde terrein neemt de professie van de sociaal werker onder de loep. Men verricht onderzoek naar de identiteit van de sociaal werker, de beroepsopvatting, of de percepties over de eigenheid van de sociaal werker tegenover andere praktijkdisciplines, zoals huisartsen, verpleegkundigen, psychologen of therapeuten (Fargion, 2008;Scholte, 2010;Weiss-Gal & Welbourne, 2008). Een belangrijke vraag binnen dit onderzoek betreft de identiteit van de sociaal werk professie.…”
Section: H E T T E R R E I Nunclassified
“…There are a number of claims made in the literature to define social work models, the social work purpose, provide a set of values in codes of conduct and describe 'ideal' types of social work. Whilst a considerable amount of research has been undertaken in the attempt to define what social work is and what social workers do, little consensus has been reached (Barnes & Hugman, 2002;Fargion, 2008;Gibelman, 1999). Nonetheless, a significant proportion of contemporary work refers to a variation of Payne's triangle model (Payne, 2005, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Fargion's (2008) qualitative study explored themes present in Italian practitioners' representations of social work through focus groups. She found that Italian social work practitioners reflect the ongoing micro-macro debates present in literature that seek to define social work as a structural or individual pursuit (Fargion, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations